PUSAT SENI LUKIS DI KOTA PONTIANAK - Febriana, Febriana; Caesariadi, Tri Wibowo; Kalsum, Emilya (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2026)
Painting art continues to develop in Indonesia, including in the city of Pontianak, West Kalimantan, as reflected in the growing activities of painters, art communities, and various events such as exhibitions, marketing activities, seminars, workshops, and competitions. In addition to conventional painters, digital painters have also emerged, offering potential for collaboration between the two fields. However, the absence of adequate facilities remains a major obstacle to the development of painting art in Pontianak. Therefore, the design of a Painting Art Center in Pontianak is needed to support the growth of local artistic potential. The design process involves several methods, including determining the object of design—namely the painting art center—collecting data through observation, interviews, and literature studies, followed by analysis and design stages that produce both internal and external design concepts. The main idea and theme adopted is “A Vibrant & Thriving Center,” which represents a space where painting art and its community can grow together, emphasizing adaptiveness, flexibility, interactivity, and visual appeal.The design outcomes include a painting art center area tailored to the needs of painters, flexible spatial layouts with minimal permanent partitions, and facilities that encourage interaction through garden plazas, discussion spaces, and community areas positioned near recreational zones. The building is also designed with a distinctive organic form to strengthen the identity of the complex. Overall, the design of the Painting Art Center in Pontianak aims to create a space that accommodates and stimulates the enthusiasm and creativity of painters, while also increasing public interest and appreciation for painting art in Pontianak.